2008
DOI: 10.1007/s10682-008-9246-4
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stress and quantitative genetic variation in butterfly wing characteristics

Abstract: Butterfly wing characteristics are extensively used as model system in studies of development, quantitative genetics and phenotypic plasticity. In spite of its evolutionary relevance, however, the effect of stress on the expression of genetic variation itself has only rarely been studied. In this paper, we explore genetic variation of wing characteristics of the Speckled wood Pararge aegeria along a host plant drought stress gradient. Forewing area, basal and distal degree of melanization and the area of five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…Our study is in accordance with others in indicating that insect morphology might be modifi ed by environmental changes, especially in terms of an increased variability in phenotype (Dennis & Shreeve, 1989;Berwaerts, 1998;Talloen et al, 2009;Gibbs et al, 2011). Indeed, the recent work of Xi et al (2015) support the hypothesis that there has been changes in morphology resulting from recent changes in climate.…”
Section: Discussionsupporting
confidence: 92%
“…Our study is in accordance with others in indicating that insect morphology might be modifi ed by environmental changes, especially in terms of an increased variability in phenotype (Dennis & Shreeve, 1989;Berwaerts, 1998;Talloen et al, 2009;Gibbs et al, 2011). Indeed, the recent work of Xi et al (2015) support the hypothesis that there has been changes in morphology resulting from recent changes in climate.…”
Section: Discussionsupporting
confidence: 92%
“…the ability to produce environmentally induced morphologies) evolved from such cryptic genetic variation? Although the heritability of plasticity can be measured (Laurila et al 2002;Relyea 2005;Gomez-Mestre et al 2008;Talloen et al 2009; electronic supplementary material, appendix S4), it is unclear whether selection acts on reaction norms per se. Indeed, empirical studies have found that plasticity may fail to respond to artificial selection in the presence of genetic variation for the reaction norm (van Kluenen et al 2002) and, conversely, evolve in spite of a strong genetic correlation between traits in alternate environments (Beldade et al 2002;Czesak et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…butterflies, climate change, host plant, multiannual drought, phenotypic biomarker, Pieris napi, thermal buffering Hirst, & Atkinson, 2012;Kingsolver, 2009;Nygren, Bergström, & Nylin, 2008;Sheridan & Bickford, 2011;Talloen, Van Dongen, Van Dyck, & Lens, 2009). Therefore, it is likely that an extensive quantification of plastic phenotypic traits in declining and non-declining natural populations could indicate their different vulnerability to warmer conditions.…”
Section: Introductionmentioning
confidence: 99%